2019
DOI: 10.1155/2019/1470105
|View full text |Cite
|
Sign up to set email alerts
|

Giant Vulvar Condylomata: Two Cases and a Review of the Literature

Abstract: Introduction. Giant vulvar condyloma is usually associated with the HPV subtypes 6 and 11 and is characterized by excessive growth of verrucous lesions on the genitals and/or perianal region. It may be observed in sexually inactive as well as sexually active women. Immunosuppression plays an important role in the development of the disease. Patients and Methods. We report two cases of giant vulvar condyloma together with the review of the literature. Results. One case was a 21-year old sexually inactive woman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Around 80% of those infected are between 17 and 33 years old, with a peak age group of 20-24 years. In women, the lesions may be found on the vulva, in the vagina, and on the cervix [8], [9]. The incubation period is approximately 5-6 months in women.…”
Section: Discussionmentioning
confidence: 99%
“…Around 80% of those infected are between 17 and 33 years old, with a peak age group of 20-24 years. In women, the lesions may be found on the vulva, in the vagina, and on the cervix [8], [9]. The incubation period is approximately 5-6 months in women.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases associated with immunodeficiency conditions have been described. Gungor et al [ 15 ] reported the case of a 22-year-old smoker woman with type 1 diabetes, who was sexually inactive treated with resection and without recurrence at 12 months of follow-up, and suggests that aggressive local growth could be related to immunosuppression.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Cases have also been reported in which the association of GCA with cervical intraepithelial neoplasia (CIN) is described [ 15 ]. Liu et al [ 22 ] reported the coexistence of GCA with verrucous carcinoma of the vulva and suggested that in the event of a GCA resistant to treatment and a long course of the disease, a biopsy should be performed due to this possibility.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Human papilloma virus (HPV) is primarily transmitted through sexual contact, which can be identified in the age of between 18 and 28 years old. Clinical manifestations of condyloma acuminata are usually associated with infection of HPV subtype 6 and 11, in the form of massive growth of verrucosa on the genital [2], however, some cases are asymptomatic [3]. The high incidence of HPV infection in pregnant women is associated with the increase in the immune response during pregnancy [4], also caused by pregnancy hormones [5].…”
Section: Introductionmentioning
confidence: 99%